PERFORMANCE TESTS OF COMPOST AND PADDY SOIL MEDIA BED ON GHG (CH4 & CO2) ELIMINATION IN LANDFILL - Purwanta, Wahyu (Jurnal Rekayasa Lingkungan)
One method to reduce emissions of CH4 from municipal solid waste landfill is to modify the final cover layer. Methane (CH4) oxidation by methanotrophs bacteria in the soil cover layer can reduce the concentration of the CH4 emission to the atmosphere. Through field experiments, tested the effect of media bed thickness, moisture and nutrient content in the form of a media bed type that is compost and paddy soil. In general, the efficiency of oxidation by using compost media is higher than the use of paddy soil cover. For both media bed, moisture content 30% more efficient in the oxidation of CH4 compared to 20%. Moisture content determines the rate of gas diffusion between media bed with its gas phase (CH4 and O2). While for a thickness of 25 cm also produced a higher oxidation rate than the 15 cm because of the methanotrophs population.keywords: landfill gas; biofiltration; methane oxydation